1989
DOI: 10.1007/bf00305065
|View full text |Cite
|
Sign up to set email alerts
|

Creatine kinase isozyme expression in embryonic chicken heart

Abstract: The distribution pattern of creatine kinase (EC 2.7.3.2) isozymes in developing chicken heart was studied by immunohistochemistry. Creatine kinase M, which is absent from adult heart, is transiently expressed between 4 and 11 days of incubation. During that period, numerous muscular cells in the roof and septum of the atrium, in the interventricular septum and on top of the trabeculae cordis and at the rim of the outflow tract stain strongly with a polyclonal antibody that is specific for the M subunit. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Such differentiation can also be derived from the indirect comparison in our immunoblotting and the immunocytochemical experiments by (Kullmann et al 2009) using AB15688. Apparently, more epitopes are exposed after extensive denaturation as done in immunoblots than in immunocytochemical or immunohistochemical studies, as previously also demonstrated for antibodies against creatine kinase (Lamers et al 1989). Studies on glutamic acid decarboxylase also support the notion that linear structures expose different epitopes for antibody recognition than those found in complex threedimensional conformations (Al-Bukhari et al 2002).…”
Section: Discussionmentioning
confidence: 72%
“…Such differentiation can also be derived from the indirect comparison in our immunoblotting and the immunocytochemical experiments by (Kullmann et al 2009) using AB15688. Apparently, more epitopes are exposed after extensive denaturation as done in immunoblots than in immunocytochemical or immunohistochemical studies, as previously also demonstrated for antibodies against creatine kinase (Lamers et al 1989). Studies on glutamic acid decarboxylase also support the notion that linear structures expose different epitopes for antibody recognition than those found in complex threedimensional conformations (Al-Bukhari et al 2002).…”
Section: Discussionmentioning
confidence: 72%
“…In particular, CK-M expression may be an early enzymatic parameter of the developmental appearance of the ventricular conductive tissue. In all other species investigated (Forsgren et al 1983;Lamers et al 1989;Wessels et al 1990a), CK-M expression is initially found in the subendocardial layer of the ventricular walls and in the trabeculae. Subsequently, a high concentration of CK-M accumulates in the bundle branches, i.e.…”
Section: Immunohistochemical Distribution Of the Creatine Kinase Subumentioning
confidence: 99%
“…Subsequently, a high concentration of CK-M accumulates in the bundle branches, i.e. the presumably rapidly conducting structures of human, bovine and chicken embryos (Forsgren et al 1983;Lamers et al 1989;Wessels etal. 1990a), whereas the atrioventricular junction, atrioventricular node and the proximal part of the bundle of His, i.e.…”
Section: Immunohistochemical Distribution Of the Creatine Kinase Subumentioning
confidence: 99%
“…181 Creatine kinase-M is virtual absent from the flanking segments (IFT, AVC, and OFT) and was much higher in the TVC than the CVC. Higher creatine kinase-M levels are also found to be associated with the developing ventricular conduction system in chicken, 182 rat, 183 and bovine 184 hearts.…”
Section: Creatine Kinasementioning
confidence: 93%